Geographies of Schooling - Jahnke, Holger; Kramer, Caroline; Meusburger, Peter (Knowledge and Space, 2019)
This open access book explores the complex relationship between schooling as a set of practices embedded in educational institutions and their specific spatial dimensions from different disciplinary perspectives. It presents innovative empirical and conceptual research by international scholars from the fields of social geography, pedagogy, educational and social sciences in Germany, the United Kingdom, France, Czechia, Hungary, Austria, Switzerland, Norway and Canada. The book covers a broad range of topics, all examined from a spatial perspective: the governance of schooling, the transition processes of and within national school systems, the question of small schools in peripheral areas as well as the embeddedness of schooling in broader processes of social change. Transcending disciplinary boundaries, the book offers deep insights into current theoretical debates and empirical case studies within the broad research field encompassing the complex relationship between education and space.